Pengembangan Formulasi Sediaan Gummy Candy dengan Variasi Konsentrasi Gelatin Sebagai Gelling Agent - Vriezka Mierza; Shinta Puspa Dwiyanti; Mulidini Mulidini; Salsabila Granadha Nibullah; Zuyyinna Alya Abbas (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Gummy candy is candy that is usually made from fruit juice or water and a gelling agent, has a clear, transparent appearance and has a chewy texture. The purpose of this study was to determine the formulation and compare the levels of gelatin as a gelling agent in the formation of a gummy candy chewy texture. The research method used was to conduct a literature study on several credible journals with criteria for journals in the last 10 years regarding the formulation of gummy candy with gelatin as the gelling agent. The results obtained are the use of gelatin as a gelling agent that can be combined with pectin and glycerin. The best concentration of the combination of gelatin and pectin is in the range of 15-20%, while the best concentration of the combination of gelatin and glycerin is in the range of 25-30%. So it can be concluded that the use of gelatin as a gelling agent and pectin as a chewiness enhancer requires a lower concentration compared to gelatin and glycerin to produce gummy candy which has the preferred level of elasticity.